Sketch-based data plane hardware model for software-defined measurement - Mian DAI; Guang CHENG (Tongxin xuebao)
A sketch-based data plane hardware model for software-defined measurement was introduced,and it was implemented in the programmable network device NetMagic.A generic sketch model for collecting flow-level data using high-speed memories on the FPGA was proposed,the control plane collected and cached the data for further process.Count-min sketch and 2-universal hash functions in the SRAM of FPGA for real-time traffic counting of high-speed traffic were implemented; Bloom filter was used to rebuild the original 5-tuple data which solved the irreversibility of sketch.The CERNET backbone trace to evaluate the prototype system was used,the result shows that it has the ability to use the limited hardware resource to measure a large amount of network traffic data with a proper measurement accuracy at the same time.